The relationship between historiography and power in Ismaili discourse A case study of the Fatimid government - Ali Babaei Siab (تاریخ نگری و تاریخ نگاری, 2022)
Ismaili historiography differs fundamentally differ from the prevailing current of traditional historiography in that it emphasises its own theoretical philosophy in some aspects such as the driving forces of history, patterns of historical movement, and the idea of progress in history. This problem has directly affected the scope of historiography, the subject, purpose, approach and method of historiography by the historians of the Ismaili religion, the works of the early Ismaili historians and consequently the Fatimids, in a way that has led many researchers in the field to believe that the Ismailis Basically do not have their own historiographical tradition. The topic we will explore in this article is the analysis of the relationship between historiography and political power in the Fatimid period and its impact on the approach and subject of historiography of Fatimid historians in different periods of the political life of this government. The results of this research show that the political developments surrounding the position of the Imam as a central point in Ismaili thought have caused changes in the approach and topic of historiography in the Fatimid period. The research method in this article is qualitative content analysis and data extraction based on the selection of meaningful statements from library sources.